2018
DOI: 10.1007/978-3-319-91602-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Interface Problems of Agile in a Non-agile Environment

Abstract: Abstract. Agile is the widespread software development approach. But many projects are still working with traditional methods. In addition, non-technical business units continue working in traditional ways. Thus, problems arise on the interface of agile and traditional due to their fundamental differences. To prevent potential problems, one must be aware of the existing interfaces and common pitfalls. Based on a literature search and workshops, we identified existing interfaces, collected and grouped problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…More interfaces not explicitly addressed by SAFe exist, e.g., synchronizing agile development with a product line approach [ 18 ]. An initial overview of the dependencies of agile teams on their environment is provided by [ 2 ]. A possible next step for research would be to refine this classification of interfaces to understand what concrete dependencies exist in order to be able to find solutions.…”
Section: Discussion and Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…More interfaces not explicitly addressed by SAFe exist, e.g., synchronizing agile development with a product line approach [ 18 ]. An initial overview of the dependencies of agile teams on their environment is provided by [ 2 ]. A possible next step for research would be to refine this classification of interfaces to understand what concrete dependencies exist in order to be able to find solutions.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…Challenges mentioned at the workshop A-Teams in 2019 [ 5 ] were that teams have “too many dependencies to others”, a “lack of organizational support”, and “part-time resources”, which are all “interface problems” [ 2 ]. In the 2018 A-teams workshop [ 6 ], concerns like “coordination”, “organizational context supporting autonomy”, or “leadership” also address interface problems and were rated as having the highest priority.…”
Section: Motivation and Research Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Theobald and Diebold 29 and Kusters et al 30 investigate the problems at the interfaces between agile and traditional processes, yet only here a parallel existence of both processes is considered. Theobald et al 29 identified in the context of a workshop problems on the interfaces between the team and the project, the project and the organization, to the customer, to subcontractors, and to regulatory authorities. Kusters et al 30 conducted a systematic literature review, shown in Table 1.…”
Section: Background and Related Workmentioning
confidence: 99%